The building up of new imbalances in China: The dilemma with 'rebalancing' - Helmut Wagner (University of Hagen, Center for East Asia Macro-economic Studies (CEAMeS), 2016)
This paper offers a theoretical basis for the concept of rebalancing and applies it to China, where it is currently a topical issue. Rebalancing here means the correction of economic and social imbalances built up during industrialization. This correction is accompanied by a structural transformation towards a more inward- and consumption-driven growth path, associated with growth slowdown. Attempts to mitigate this growth slowdown by either retarding this structural reform process or by using expansionary stimulus programmes as done over the past decade in China create new imbalances that have to be corrected (rebalanced) again. Managing these multiple rebalancing tasks together is a tremendous undertaking, as this paper shows.
urn:nbn:de:hbz:708-dh4700
Keywords: F41; O10; O40; O53; 330; rebalancing; China; development strategy